Management of postoperative pain in patients undergoing total knee - Sonia Marchán Espinosa; Amparo Gómez-Rico Pareja (Fundación para el Desarrollo de la Enfermería, 2011)
The postoperatory pain after total prothesis of knee is a special type of agony, of great repercussion in the health area, since it affects the surgical patients who suffer it, the family that "suffer" together with the patient, the responsible doctors, the nursing personnel and the involved institutions. Aim: To value the pain degree for the immediate postoperatory of the prothesis of knee surgical patients during his stay at the Post-anesthesic Recovery Unit.Material and method: There was realized a descriptive study at the Valdepeña´s Hospital at the Post-anesthesic Recovery Unit for 7 months. The sample was formed by the prothesis of knee surgical patients during this period. There was designed a multiple answers questionnaire to which the patients answered during his stay in the unit and there was in use as instrument of measure of the pain the visual analogical scale.Results: 50 % of the patients suffered an intense pain after the anesthesic effect disappear. Almost the totality of the patients (90 %) needed an analgesic rescue. In spite of it, the satisfaction that the patients expressed with the relief of his pain was very high.Conclusions: The patients experience high pain levels during the immediate postoperatory. The results reveal the need to design analgesic protocols more adapted to the individual patients need.